STRATEGI PENGEMBANGAN USAHA BERAS SEHAT PADA CV PURE CIANJUR DI KABUPATEN CIANJUR (Forum Agribisnis, 2019)
The objectives of this research are to identify the factors that exist in the internal and external environment that become the strengths, weaknesses, threats, and opportunities for CV Pure Cianjur, formulate alternative strategies and determine the priority strategies that can be run CV Pure Cianjur in developing business, mapping program recommendations from alternative strategies in the development of healthy rice business on CV Pure Cianjur. The method research use internal and eksternal environment analysis, formulation strategy using SWOT analysis, weighting strategy priorities through preparation of hierarchy based on the SWOT framework (A’WOT) and the program recommendation made by the strategic architecture model. Internal factors of company : strength (S) is the quality of products (0,377) and weaknesses factor (W) is discontinuity of raw material supply (0,402). External factors of company opportunities (O) is the natural resources of Cianjur Regency (0,181) and threats (T) factors is the substitution products (anorganic rice) (0,349). Priority of strategic alternatives is conduct preparation and registration for organic certification (0,299). Implication of alternative strategies is devided into two groups, where is 11 programs recommendation that run gradually and 7 programs recommendation that run regularly.